Nonlinear Magnetoelectric Response of Fe(73.5)Cu(1)Nb(3)Si(13.5)B(9)/Piezofiber Composite for a Pulsed Magnetic Field Sensor - Lu, Caijiang (Materials (Basel), 2019)
In this paper, we report the nonlinear magnetoelectric response in a homogenous magnetostrictive/piezoelectric laminate material. The proposed magnetoelectric stack Fe(73.5)Cu(1)Nb(3)Si(13.5)B(9)/piezofiber is made up of high-permeability magnetostrictive Fe(73.5)Cu(1)Nb(3)Si(13.5)B(9) foils and a piezoelectric Pb(Zr, Ti)O(3) fiber composite. The time dependence of magnetoelectric interactions in the Fe(73.5)Cu(1)Nb(3)Si(13.5)B(9)/piezofiber structure driven by pulsed magnetic field was investigated in detail. The experimental results show that the magnetoelectric effect is strongly dependent on the external bias magnetic and pulsed magnetic field parameters. To detect the amplitude of a pulsed magnetic field, the output sensitivity reaches 17 mV/Oe, which is excited by a 100 μs width field. In addition, to measure the pulsed width, the output sensitivity reaches 5.4 mV/μs in the range of 0–300 μs. The results show that the proposed Fe(73.5)Cu(1)Nb(3)Si(13.5)B(9)/piezofiber sensor is ideally suited for pulsed magnetic field measurement.